2017
DOI: 10.2147/ijn.s140569
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine-mediated poly(lactic-<em>co</em>-glycolic acid)&nbsp;nanoparticles containing fluorofenidone for the treatment of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis is a progressive, fatal lung disease with poor survival. The advances made in deciphering this disease have led to the approval of different antifibrotic molecules, such as pirfenidone and nintedanib. An increasing number of studies with particles (liposomes, nanoparticles [NPs], microspheres, nanopolymersomes, and nanoliposomes) modified with different functional groups have demonstrated improvement in lung-targeted drug delivery. In the present study, we prepared, characterized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 84 publications
3
14
0
Order By: Relevance
“…The OS reduction is followed by a decrease of cytotoxicity from (22.4 ± 3.8)% to (7 ± 2.9)%, confirming the role of PTS in spd-SNPs internalization. These experiments suggest that spermidine functionalization selectively acts on particle transport into MeWo cells by a PTS-mediated endocytosis process, resulting fully consistent with data reported by recent studies 70 , 71 .…”
Section: Functional Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…The OS reduction is followed by a decrease of cytotoxicity from (22.4 ± 3.8)% to (7 ± 2.9)%, confirming the role of PTS in spd-SNPs internalization. These experiments suggest that spermidine functionalization selectively acts on particle transport into MeWo cells by a PTS-mediated endocytosis process, resulting fully consistent with data reported by recent studies 70 , 71 .…”
Section: Functional Studiessupporting
confidence: 92%
“…Specifically, if PTS selectively takes part to particle uptake, it is expected that, after blocking its function, cellular uptake would quantitatively decrease. Data confirm PTS involvement in particle internalization, mainly for spd-SNPs, indicating an active uptake via spermidine-PTS affinity 70,71 .…”
Section: Functional Studiessupporting
confidence: 58%
“…This method provides the ability to specifically deliver antiproteases to the luminal surface of the respiratory epithelium within the airway surface fluid. The amount of antiprotease delivered to the apical surface would be protective in the early stages of CF, but it may not be sufficient to prevent the late‐stage CF lung's (Tang et al, ).…”
Section: Neutrophil‐targeted Drug Delivery In Respiratory Diseasesmentioning
confidence: 99%
“…Drug-delivering nanoparticles displaying at their 57 surface reconnaissance molecules for overexpressed targets in fibrosis-associated cells may represent another approach to solve some of the problems of off-target side-effects, as shown in a rat model of pulmonary fibrosis. 196 Drugs able to modulate physiological pathways other than the TGF-β, such as oxidative stress, lipids, enzymes, kinases or peptide receptors, have been evaluated. Most clinical trials were disappointing, although the molecules had shown efficacy in preclinical animal models of the diseases.…”
Section: Conclusion and Perspectivementioning
confidence: 99%